Effect of HPMC Concentration and Liquid Addition Method on Granules Properties using High-Shear Wet Granulator - Shahad Qutaiba Waleed; Ali Zainalabbdeen Asker Al-Hassn (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Enhancing the physical properties of medicinal powders is largely dependent on the granulation process. This study investigates the interaction between the concentration of hydroxypropyl methylcellulose (HPMC) and the liquid addition technique on the distribution of granule sizes and its porosity in a high-shear mixer setup. Both a 5% HPMC solution and distilled water (0% HPMC) were employed in the calcium carbonate powder granulation process. The results showed that while excessive liquid addition using the pouring method led to uneven growth and agglomeration, an increase in binder viscosity improved granule homogeneity. On the other hand, the syringe method provided more uniform granules, showing its effectiveness in achieving controlled nucleation and growth. The impact of these parameters on granule characteristics was further supported by the design of response surface plots and models made easier by statistical analysis using Design-Expert software. These findings provide important information for improving wet granulation methods in the manufacturing of pharmaceuticals, especially with regards to guaranteeing the stability and uniformity of the final product.